Application of Information Technology and Learning Motivation during the Covid-19 Pandemic - Nurul Hikmah Kartini; Chandra Anugrah Putra; Muhammad Noor Fitriyanto (Jurnal Dedikasi, 2020)
The purpose of this study was to utilize information technology and increase learning motivation during the Covid 19 period. The subjects of this study were teachers in the city of Palangkaraya. The research stages were initial observation and socialization of activities, opening of activity registration, making modules, implementing activities, giving structured assignments, evaluating, publishing, monitoring, and reporting. The conclusion is E Learning using edmodo is an affective way of implementing distance learning, the very good and enthusiastic teacher input indicates that edmogo is a solution to the use of information technology during the Covid 19 pandemic, The learning motivation that students feel needs to be improved in the first way is to increase teacher motivation in teaching, with high teacher motivation in teaching, the teacher will try to develop their skills in selecting and making interesting teaching materials.